Threat assessment mathematical model for potentially dangerous objects of critical infrastructure in the combat zone - Murasov, R.K.; Kurtseitov, T.L.; Chumachenko, S.M.; Lunova, O.V.; Pyrykov, O.V.; Lunov, A.O. (Інститут програмних систем НАН України, 2023)
The paper examines a mathematical model of threat assessment for potentially dangerous objects of critical infrastructure in the combat zone. Using the theory of graphs and the theory of probability, an approach is proposed that allows obtaining quantitative estimates and conducting an analysis of possible scenarios of the development of an emergency situation. This work will be useful in the development of different classes of ecological and man-made threat assessment mathematical models for critical infrastructure facilities in the war zone. Prombles in programming 2022; 3-4: 446-454